2017
DOI: 10.1123/ijspp.2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Neurological Insult in Competitive Deep Breath-Hold Diving

Abstract: This report highlights the possibility of neurological insult, eg, stroke, due to cerebral arterial gas embolism as a consequence of decompression stress after deep breath-hold dives. Thus, stroke as a clinical presentation of cerebral arterial gas embolism should be considered another risk of extreme breath-hold diving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Decompression sickness (DCS) or "Taravana" can occur in breath-hold divers, especially those diving repetitively (e.g., spearfishing, safety divers, and/or use of underwater scooters) and those performing extreme depths (reviewed in; Cross, 1965;Paulev, 1965;Rahn and Yokoyama, 1965;Schipke et al, 2006;Fitz-Clarke, 2009;Lemaitre et al, 2009;Moon and Gray, 2010;Dujic and Breskovic, 2012). The pathology of DCS, including its manifestation and risk factors have been extensively reviewed elsewhere (Brubakk and Neuman, 2003); however, in breath-hold divers, symptoms can range from dizziness, nausea, thoracic/skin/joint pain, hemiplegia, paresis, dysarthria, vertigo, and unconsciousness, with short-to long-term prognoses (Cross, 1965;Schipke et al, 2006;Cortegiani et al, 2013;Tetzlaff et al, 2017). The consequences of DCS are related to the affinity of certain tissues and the rate at which they uptake nitrogen.…”
Section: Risk Of Decompression Sicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Decompression sickness (DCS) or "Taravana" can occur in breath-hold divers, especially those diving repetitively (e.g., spearfishing, safety divers, and/or use of underwater scooters) and those performing extreme depths (reviewed in; Cross, 1965;Paulev, 1965;Rahn and Yokoyama, 1965;Schipke et al, 2006;Fitz-Clarke, 2009;Lemaitre et al, 2009;Moon and Gray, 2010;Dujic and Breskovic, 2012). The pathology of DCS, including its manifestation and risk factors have been extensively reviewed elsewhere (Brubakk and Neuman, 2003); however, in breath-hold divers, symptoms can range from dizziness, nausea, thoracic/skin/joint pain, hemiplegia, paresis, dysarthria, vertigo, and unconsciousness, with short-to long-term prognoses (Cross, 1965;Schipke et al, 2006;Cortegiani et al, 2013;Tetzlaff et al, 2017). The consequences of DCS are related to the affinity of certain tissues and the rate at which they uptake nitrogen.…”
Section: Risk Of Decompression Sicknessmentioning
confidence: 99%
“…It is perhaps not surprising that intravascular bubbles have been reported following spearfishing, where short surface times and the repetitive dives occur with often insufficient times to allow nitrogen clearance (Cialoni et al, 2016). Although this observation is not a universal finding (Boussuges et al, 1997;Gargne et al, 2012), arterial gas embolism following breath-hold diving has been implicated in stroke risk (Tetzlaff et al, 2017). Ultimately, modeling has suggested that the risk of decompression sickness up to 100 meters is quite low, but increases non-linearly to 5-7% at 230 m, where total lung collapse is anticipated to occur (Fitz-Clarke, 2009).…”
Section: Risk Of Decompression Sicknessmentioning
confidence: 99%
“…The tremendous physiological demands imparted on the human body by traditional breath-hold diving are well described and include effects on the cardiovascular, pulmonary, neurological, and renal systems (Dujicv & Breskovic, 2012;Gren et al, 2016;Marabotti et al, 2013;Mijacika & Dujic, 2016;Pendergast & Lundgren, 2009;Tetzlaff, Schöppenthau, & Schipke, 2017). In addition to these physiological challenges, technical divers may be at an increased risk for DCS, Taravana syndrome, AGE, central nervous system (CNS) oxygen toxicity, and barotraumatic injuries of the middle ear, eyes, and sinuses.…”
Section: Pathophysiology and Risksmentioning
confidence: 99%
“…Does it help to regulate it voluntarily? The awareness of internal sensation during a dive is important because only the inner feelings prompt the free diver to float up when necessary, due to the risk to health and life [9].…”
Section: Introductionmentioning
confidence: 99%